Cuts to Beck's novel Currency. (August 2015) - Beck, Sarah
This is an excerpt from Sarah Beck's novel Currency . Created as a gift of thanks to the late Kurt Vonnegut, Currency is a humorous story about money, art, fakes and sea pirates. The novel is Sarah's self-reflexive take on social economic exchanges both within and without the art world. Currency is an odd document – it seeks true interdisciplinarity not just between mediums but in the search for a plurality of possible ways to express and to approach artistic research. Chapter-by-chapter, the self-reflexive narrative guides the reader through musings on the experience of the creation of ephemeral artworks using colloquial language, illustrations, jokes and parables. Written as her master's thesis, Sarah was obliged to attach an academic explanation, which she has maintained as the last part of her book. Art is a hell of a commodity, and Currency is a hell of a book. Visitsarahbeck.com for more information about Currency and her artistic practice.